Teachers’ experiences with the Back2School intervention—a pilot study addressing problematic school absenteeism - Bania, Elisabeth Valmyr; Nilsen, Toril Sørheim; Thastum, Mikael; Ingul, Jo Magne; Havik, Trude (Frontiers in Psychology, 2025)
IntroductionSchool absenteeism represents a concern for students, educators, and parents alike. Teachers’ involvement is vital to students’ school life. Consequently, integrating schools and teachers effectively in absenteeism interventions is of great importance. However, few studies have investigated teachers’ perspectives on participating in manual-based, indicated interventions to promote school attendance. This study aimed to explore teachers’ experiences with the manual-based Back2School (B2S) intervention, which is based on cognitive behavioural therapy (CBT).MethodsSeven primary and lower secondary school teachers agreed to participate in individual interviews following their involvement in the intervention. These teachers engaged in various aspects of the intervention, including data collection, school sessions, and school meetings involving students, parents, and B2S group leaders.ResultsThe results indicate that some of the informants experienced increased competence and self-efficacy regarding school absenteeism following the intervention, while other informants did not have this experience.DiscussionThere is a need for more clarity and enhanced teacher involvement in future B2S interventions.